Combined epithelial marker analysis of tumour budding in stage II colorectal cancer - Khadija Slik; Sami Blom; Riku Turkki; Katja Välimäki; Samu Kurki; Harri Mustonen; Caj Haglund; Olli Carpén; Olli Kallioniemi; Eija Korkeila; Jari Sundström; Teijo Pellinen (United Kingdom, 2022)
Tumour budding predicts survival of stage II colorectal cancer (CRC) and has been suggested to be associated with epithelial‐to‐mesenchymal transition (EMT). However, the underlying molecular changes of tumour budding remain poorly understood. Here, we performed multiplex immunohistochemistry (mIHC) to phenotypically profile tumours using known EMT‐associated markers: E‐cadherin (adherence junctions), integrin β4 (ITGB4; basement membrane), ZO‐1 (tight junctions), and pan‐cytokeratin. A subpopulation of patients showed high ITGB4 expression in tumour buds, and this coincided with a switch of ITGB4 localisation from basal membrane of intact epithelium to the cytoplasm of budding cells. Digital image analysis revealed that tumour budding with high ITGB4 expression in tissue microarray (TMA) cores correlated with tumour budding assessed from H&E whole‐sections and independently predicted poor disease‐specific survival in two independent stage II CRC cohorts (hazard ratio (HR) =4 .50 (95% CI=1.50–13.5), n=232; HR=3.52 (95% CI=1.30‐9.53), n=72). Furthermore, digitally obtained ITGB4‐high bud count in random TMA cores associated better with survival outcome than visual tumour bud count in corresponding H&E stained samples. In summary, the mIHC‐based phenotypic profiling of human tumour tissue shows strong potential for the molecular characterisation of tumour biology and for the discovery of novel prognostic biomarkers.